Application of Polyglycolic Acid/Poly (Lactic‐co‐glycolic Acid) in Thread Embedding Acupuncture for Obesity: New Strategies and Challenges - Wang J; Cao K; Chen Z; Lyu T; Xia Q; Zhu X; Liu L; Li B (Diabetes, Metabolic Syndrome and Obesity, 2025)
Jinkun Wang,1,2,* Kangdi Cao,2,* Zhaoyi Chen,1,* Tianli Lyu,1 Qiuyu Xia,1 Xiaoyun Zhu,3 Lu Liu,1 Bin Li1 1Department of Acupuncture and Moxibustion, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing Key Laboratory of Acupuncture Neuromodulation, Beijing, People’s Republic of China; 2Department of Graduate School, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 3Department of Laboratory of Diabetes, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lu Liu, Beijing Hospital of Traditional Chinese Medicine, No. 23, Art Museum Back Street, Dongcheng District, Beijing, People’s Republic of China, Email lululalavictor1985@126.com Bin Li, Beijing Hospital of Traditional Chinese Medicine, No. 23, Art Museum Back Street, Dongcheng District, Beijing, People’s Republic of China, Email libin@bjzhongyi.comAbstract: Obesity has become a prominent global public health concern, leading to the development of numerous diseases such as cardiovascular diseases, type-2 diabetes mellitus (T2DM), cancer, and several system diseases. In recent years, thread embedding acupuncture (TEA) has gained popularity as a novel and promising approach to obesity management. This method extends the traditional principles of acupuncture by embedding absorbable threads such as polyglycolic acid (PGA) and poly (lactic-co-glycolic acid) (PLGA) into acupoints. Currently, there has been no review of TEA in obesity management applications. This review is to discuss the clinical applications, mechanisms, new strategies and challenges of PGA/PLGA thread embedding acupuncture in obesity treatment. We conducted a comprehensive search of PubMed, Web of Science, and Embase databases using keywords such as thread embedding acupuncture, acupoint catgut embedding, obesity, and obese, covering the period from inception to 2024. Clinical studies have shown that TEA could significantly reduce weight, waist circumference, and appetite in obese patients. The therapy could modulate systemic inflammation and enhance adipocyte metabolic capacity. Additionally, TEA regulates gut microbiota composition and impacts neuroendocrine pathways, enhancing hypothalamic function and appetite control via leptin receptor activation and energy homeostasis modulation. Despite its therapeutic potential, there are challenges, such as no standard rules for acupoint selection, embedding depth, and treatment frequency. Herein, we suggest the advancements and limitations of PGA/PLGA thread embedding acupuncture. It points out its use for solving problems in obesity treatment and its chance to become a practical and new method in clinics.Keywords: PGA, PLGA, thread embedding acupuncture, obesity, mechanism